On the use of the quality function deployment matrix for flexible and quantitative prioritization - Domingos, André S. (2022)
The QFD methodology is totally directed to the client instead of the product, wherein the effort from all the involved departments allows the match between the client’s requirements and the offered product. Therefore, it is necessary to determine the engineering characteristics that aim at satisfying those customer attributes. These engineering characteristics must be measurable, in order to provide analysis and optimization opportunities. Afterwards, the prioritization of these engineering characteristics is carried out so that they are performed in the most efficient way. Throughout the paper, the authors propose the design of a new simple, flexible and quantitative methodology of activities prioritization. Strategic planning is introduced in the QFD methodology of organization and proposes the minimization of possible incompatibilities that may arise between its capabilities and customer requirements. Business variables are introduced at different stages of the design in order to calculate with greater precision the value resulting from the prioritization and to allow nullity or uniformity of the relative importance of customer attributes. The qualitative fulfillment of the correlations of the QFD methodology is replaced by a quantitative aspect that aims to minimize the filling of errors and interpretation when using the methodology. At the end of the paper, an example of planning the design of a smartphone using the new methodology is given.